Analisis dan Desain Data Center RSUD Arifin Achmad Pekanbaru Menggunakan Standarisasi TIA 942 - Syaputra, Alviandy; Iskandar, Iwan; Darmizal, Teddie; Novriyanto, Novriyanto; Safaat, Nazruddin (Teknik Informatika Universitas Pamulang, 2023)
Arifin Achmad Regional General Hospital (RSUD) has a large amount of patient data so it requires a data center to store and manage all the data. In this study, an analysis of the data center at RSUD Arifin Achmad was carried out using the TIA-942 standard. Based on the results of observations that have been made, it is obtained that the current condition of the data center has several shortcomings, including the electrical system that does not yet have a private generator as a redudant, the security system that is still minimal, and the room conditions that are still limited. Based on these problems, an analysis was carried out using the PPDIOO (Prepare, Plan, Design, Implement, Operate, and Optimize) Network Life Cycle Approach method with the TIA-942 standardization approach In this research, it has been carried out up to the design stage, where at the prepare stage, search and collect related information, interview experts to gain a better understanding of the TIA-942 standard, at the planning stage (plan) a comparative analysis of the current data center with the TIA-942 standard using GAP analysis, and at the design stage (design) the design of the proposed Tier 2 data center is made. The results of this study are the current condition of the data center still in Tier 1 and provide recommendations for proposals in the form of data center designs at Tier 2 in accordance with the TIA-942 standard.